Explicit vs. Implicit Auditory Displays for Managing People Flow in a Pandemic: An Exploratory Study - Kuratomo, Noko; Karic, Benjamin; Kray, Christian (Interacting with computers, 2025)
Abstract Social distancing is one of the key measures to lower infections during a pandemic. Pedestrian signage is one way to achieve this by managing the flow of people to reduce crowdedness. However, visual signs can clutter the environment and might not be noticed by pedestrians. In this paper, we propose auditory displays for managing pedestrian flow. We developed implicit and explicit sound signs, evaluated them in a user study with 16 participants and compared our results to those reported for visual signage. Our results show that auditory signs are as effective as visual signs in managing the flow of people. Although using explicit sounds tends to be more effective than using implicit sounds, our findings indicate a tendency for implicit sounds to be preferred by participants with respect to environmental comfort. Our work contributes to the understanding of auditory displays and facilitates investigating further uses beyond pedestrian flow management during a pandemic.